NEDD8 nucleates a multivalent cullin-RING-UBE2D ubiquitin ligation assembly - Baek, Kheewoong (Nature, 2020)
Virtually all eukaryotic processes are regulated by cullin-RING E3 ligase (CRL)-catalyzed protein ubiquitylation(1), which is exquisitely controlled by cullin modification with the ubiquitin (UB)-like protein NEDD8(2–6). However, how CRLs catalyze ubiquitylation, and the basis for NEDD8 activation, remain unknown. We report the cryo EM structure of a chemically-trapped complex representing the ubiquitylation intermediate whereby neddylated CRL1(β-TRCP) promotes UB transfer from the E2 UBE2D to its recruited substrate phosphorylated IκBα. The structure shows that NEDD8 acts as a nexus binding disparate cullin elements and the RING-activated UB-linked UBE2D. Concomitant local structural remodeling and large-scale CRL domain movements converge to juxtapose the substrate and ubiquitylation active site. The results explain how a distinctive UB-like protein alters the functions of its targets, and show how numerous NEDD8-dependent interprotein interactions and conformational changes synergistically configure a catalytic CRL architecture that is both robust for rapid substrate ubiquitylation and fragile to enable ensuing cullin-RING functions.